ZAGHLÛL RÂGHIB MUḤAMMAD AL-NAJJÂR’S METHODS AND PRINCIPLES OF SCIENTIFIC EXEGESIS: A Review of Tafsîr al-Âyât al-Kawniyyah fî al-Qur’ân al-Karîm - Syarifah, Umaiyatus; Fahimah, Siti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Scientific exegesis is one of the new trends in interpreting the Quran that will continue to be in demand. There are many discussions of science and Quran integration, and the rise of various works of scientific interpretation among scholars and scientists has become the real proof of it. However, some Muslim communities still doubt the validity of scientific interpretations. One of the reasons is because the source of the interpretation is relative and temporal. This evidence, of course, cannot be compared with the Quran, which is absolute. Therefore, a regulation is needed in the application of scientific interpretation. This study aims to examine and explore the methods and principles of the scientific interpretation of the Quran conducted by Zaghlûl Râghib al-Najjâr, in terms of their strengths, shortcomings, and relevance in the interpretation of the Quran. This research is considered qualitative research utilizing library research by analyzing some literatures such as books and journal articles. The results of this research show that the Zaghlûl as a Geologist, who is quite productive with the authority of science he has, does not only interpret Quran scientifically but also explains the procedure of interpretation through methods and principles of interpretation similar to scholars of tafsîr in general. In fact, he may be even be considered more specific and ideal compared to others because he not only complements but also enhances the guidelines and principles of the scientific exegesis that have been used before.